2019
DOI: 10.1002/joc.6326
|View full text |Cite
|
Sign up to set email alerts
|

Pacific and Atlantic multidecadal variability relations to the El Niño events and their effects on the South American rainfall

Abstract: This paper examines the oceanic mean states associated with the Pacific decadal oscillation (PDO) and the Atlantic multidecadal oscillation (AMO) and their relations to the El Niño (EN). The mean states refer to the simultaneous occurrences of warm (W) and cold (C) phases of these oscillations: WAMO/CPDO, CAMO/WPDO and CAMO/CPDO. In general, the sea surface temperature (SST) anomaly patterns of the mean states show a combination of the PDO and AMO related anomaly patterns in the Pacific Ocean, and the stronges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 55 publications
(105 reference statements)
4
37
0
2
Order By: Relevance
“…The years with zonal wind above the 50th percentile in the periods before and after 1997 are listed in Table 1 and represented by the dark gray bars in Figure 2. 1988-1989-1990-1993-1994-1995-1996After 1999-2003-2005-2007-2008-2010-2011 In addition, the periods before and after 1997 overlap those with distinct low-frequency SST backgrounds associated with the PDO and the AMO previously discussed by Kayano et al [40,79]. In fact, SST anomaly mean state during the 1983-1996 period shows features of the CAMO/WPDO and that during 1998-2016, of the WAMO/CPDO background (Figure 3a,b).…”
Section: Changes In Zonal Wind Indexmentioning
confidence: 82%
See 2 more Smart Citations
“…The years with zonal wind above the 50th percentile in the periods before and after 1997 are listed in Table 1 and represented by the dark gray bars in Figure 2. 1988-1989-1990-1993-1994-1995-1996After 1999-2003-2005-2007-2008-2010-2011 In addition, the periods before and after 1997 overlap those with distinct low-frequency SST backgrounds associated with the PDO and the AMO previously discussed by Kayano et al [40,79]. In fact, SST anomaly mean state during the 1983-1996 period shows features of the CAMO/WPDO and that during 1998-2016, of the WAMO/CPDO background (Figure 3a,b).…”
Section: Changes In Zonal Wind Indexmentioning
confidence: 82%
“…The 1983-1996 and 1998-2016 periods overlap the periods when the Atlantic Multi-decadal Oscillation (AMO) and the Pacific Decadal Oscillation (PDO) are in the cold AMO and warm PDO (CAMO/WPDO), and in the warm AMO and cold PDO (WAMO/CPDO), respectively. Kayano et al [40,79] showed that these SST anomaly backgrounds affect the El Niño-Southern Oscillation (ENSO) related rainfall anomalies in South America (SA) through low-frequency changes in the Walker cell. These changes in the Walker cell have been previously documented with an intensification during the last three decades [41,84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings show that the Atlantic Ocean plays an important role in modulating the rainfall and streamflow variability in the ARB. At the low frequency time scale, the SST and SLP anomalies in this Oceanic sector create the east-west SST and SLP gradients between the tropical Atlantic and eastern Pacific Oceans, which during the WAMO phase favors the La Niña event establishment [77]. Physical explanation is that the changes in the tropical Atlantic SST modify the inter-basin (tropical Atlantic and tropical eastern Pacific) pressure gradient, creating an atmospheric bridge that transmits the SST information between the basins [94,105].…”
Section: Discussionmentioning
confidence: 99%
“…Following the methodology proposed by Kayano et al [76,77], the reconstructed SST data of the 1870-2015 period were used only to support that the SST anomaly patterns during the 1965-1994 and 1995-2015 periods indeed contain, respectively, the CAMO and WAMO features [35,78]. In order to remove the climate change effects, the linear trend for the 1870-2015 of the time series at each grid point was eliminated using the method of least squares.…”
Section: Mean Sst Anomaly Patterns During the Amo Phasesmentioning
confidence: 99%